(untitled) (Fiep Bulletin - online, 2012)
In the case of sports policies, actions commonly identified are the services offered by the own public sphere, and the services offered by social sports programs, developed by private non-profit companies and funded by the public can. In these offerings, it is possible to see the evaluation of such actions by a bias mostly quantitative, seeking to serve a larger number of inhabitants, but worrying too little about the quality of service, as if the simples offer of sports, regardless of what it is done effectively, it was enough. This article aims to thereby start a discussion about a possible definition of structural categories on the concept of sport, which could serve as a basis for the offer of sports meet quantitative and qualitative demands. It was identified that way, even starting in a way that the offer of sports can be analyzed and based on five categories: regulation, body performance, competition, specialization and formality. An offer of sports that do not consider these categories would be insufficient to fulfill their purpose of ensuring the sport as a social right, since it would not be meeting the demands of practitioners, raised by his own sports nurtured.